TECHNOLOGICAL PERFORMANCE OF SINGLE-LAYER KNITTED FABRICS MADE FROM BASALT YARN WITH HIGH FIRE-RESISTANCE (International Educators Conference, 2025)
This study investigates the technological performance of single-layer knitted fabrics made from basalt yarn with high fire-resistance. The research aims to expand the range of knitted products by analyzing fabric structures and production methods to achieve lightweight surfaces and optimal bulk density. Three fabric variants (I, II, III) were tested, with key parameters such as ring pitch, ring row height, density, and loop yarn length measured. The results indicate that the surface density ranged from 258.2 g/m² to 590.2 g/m², thickness varied between 1.78 mm and 6.13 mm, and bulk density fluctuated from 96.2 mg/cm³ to 174.6 mg/cm³. The findings highlight the potential of basalt yarn in producing fire-resistant knitted fabrics, contributing to advancements in textile industry applications.